The Impact of Financial Literacy, Family Environment, and Entrepreneurial Characteristics on Entrepreneurial Interest in Yogyakarta's Community Economy - Asa, Maria Ekardis; Hermuningsih, Sri; Rinofah, Risal (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine the effect of financial literacy, family environment, and entrepreneurial characteristics on people's entrepreneurial interest in the city of Yogyakarta. The research method uses quantitative. The population in this study is aged 17-30 years. The sample used in this study was 110 people. For the tests used in this study are validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression analysis, partial test, simultaneous test and determination coefficient test. The results of this study indicate that financial literacy variables and entrepreneurial characteristics do not have a significant influence on community entrepreneurial interest. While the family environment has a significant influence on community entrepreneurial interest.